PIDGINS AND CREOLES LANGUAGES - Syarfuni (Lembaga Penelitian dan Pengabdian (LP2M) STKIP Bina Bangsa Getsempena, 2011)
A pidgin is language with no native speakers, it is not first language but it is a contact language creoles is a normal language in just about every sense. Creole has native speaker, each pidgin and Creole are well organizes of linguistic system, the sound of pidgin or creoles are likely to be a fewer and less complicated than those of related languages for example Tok pisin has only five basic vowels, Papia Kristang has seven basic vowel. The pidgin or Creole language have two theories polygenesis and relexification. The distributions of pidgin and Creole are in equatorial belt around the world, usually in place with easy success such as in the oceans and harbor.